UPAYA PENINGKATAN KEMAMPUAN MAHASISWA DALAM MATA KULIAH MATEMATIKA AWAL ANAK USIA DINI MELALUI PENGGUNAAN HASIL PENUGASAN DOSEN DI SEKOLAH - syafdaningsih syafar (Tumbuh Kembang: Kajian Teori dan Pembelajaran PAUD, 2019)
This class action research aims to improve students' ability to understand early mathematics courses in early childhood through the use of lecturer assignments at school. The study was conducted in two cycles. The action in cycle I is to give assignments to students to make plans for implementing daily learning and practice them using the learning process in kindergarten. Based on the reflection of cycle I, then in the second cycle of action, students are given the task of making an educational play tool whose material is in accordance with the design of daily learning plans that have been prepared in cycle I. The results of the study indicate an increase in students' ability towards understanding mathematics courses in early childhood which is indicated by the existence of educational play tools that have been prepared by students. At the beginning of learning (pre-test) the average score is 6.0 while the average score at the end of the learning (post-test) is 7.8. This shows that there is a significant improvement in the ability of students in early mathematics courses in early childhood through the use of lecturer assignments at school.